2004
DOI: 10.2466/pms.98.2.656-660
|View full text |Cite
|
Sign up to set email alerts
|

A Study of 60- to 89-MO.-Old Children's Skill at Writing Numerals

Abstract: The skill of writing numerals necessitates a certain developmental maturity. Studying the age at which children start to develop this skill and assessing problems they encounter while writing numerals should give direction to their training. From 8 schools a total of 267 children, ages 60 to 89 mo., were asked to write the numerals 1 to 9. Analysis showed that 80% of the children wrote most of the numerals correctly, 15% wrote inverted numerals, 2.0% wrote some numerals as letters, and 4% did not write certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At present we know that preschool children have many ideas about the number system (Brizuela, 2001), and that writing numbers is a skill that increases directly with age (Arnas, Sigirtmac, & Gul, 2004), and is linked to verbal and conceptual arithmetic (Agli & Martini, 1995;Molfese, Beswick, Molnar, & Jacobi-Vessels, 2006). Moreover, we know that preschoolers favor iconic and idiosyncratic representations, while older children are more likely to produce pictographic and symbolic forms (Hughes, 1986).…”
Section: ) Correct Use Of Arabic Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…At present we know that preschool children have many ideas about the number system (Brizuela, 2001), and that writing numbers is a skill that increases directly with age (Arnas, Sigirtmac, & Gul, 2004), and is linked to verbal and conceptual arithmetic (Agli & Martini, 1995;Molfese, Beswick, Molnar, & Jacobi-Vessels, 2006). Moreover, we know that preschoolers favor iconic and idiosyncratic representations, while older children are more likely to produce pictographic and symbolic forms (Hughes, 1986).…”
Section: ) Correct Use Of Arabic Numbermentioning
confidence: 99%
“…Arnas, Sigirtmac and Gul (2004) designed a study to investigate the ability of young (60-to 89-months-old) children to write numerals, identifying which they write incorrectly and what sort of mistakes they make in the process. They found that most children wrote numerals correctly and that their skills in writing numerals correctly increased in direct proportion to age.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation